Eugenia sphaerocarpa (Myrtaceae), a new species from Western Ghats of Kerala, India - Vadhyar, Rakesh G.; Sujana, K. A.; Benjamin, J. H. Franklin; Murthy, G.v. S. (Phytotaxa, 2020)
Eugenia sphaerocarpa, from Malabar Wildlife Sanctuary of Kozhikode district in Kerala, India, is described and illustrated. It has some morphological similarities with Eugenia codyensis, but characteristically differs by having obconic hypanthium, round staminal disk and glossy lemon-yellow coloured fruits. Palynological studies evidenced that the new species have cryptic androdioecy, a feature that is reported in Indian Eugenia for the first time.